Budownictwo drewniane w Szadku - Kowara, Sylwia (Biuletyn Szadkowski, 2009)
Szadek had been built up with timber houses and wooden buildings across the ages, before the first brick constructions appeared two hundred years ago, and have become the dominant type of building.Unfortunately, the remaining wooden construction that have not vanished and are the main existing evidence of former wood-based spatial development, are often considered to be an unimportant leftover. As a result, very few timber constructions retained their original shape and character.Today, timber buildings constitute 17 percent of Szadek’s present area of the 1378 buildings in Szadek, 240 are made of wood, including 61 used for permanent accommodation.Bad technical conditions and poor engineering quality are the main problem. In most cases it is described as bad or very bad. The lack of appropriate preservation procedures results in different types of erosion. Poor fire protection exposes the wooden objects to high risk of catching fire.Timber construction have always been connected with cultural identity of regions and their unique features and attributes. Today, they are formally governed by local authorities and should be protected as they are an important element of Poland’s tradition.